2022
DOI: 10.7759/cureus.21466
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Childhood Trauma in Psychosis and Schizophrenia: A Systematic Review

Abstract: Schizophrenia (SCZ) is a prevalent cause of disability worldwide. Distinguished mainly by psychosis, behavioral alterations could range from hallucinations to delusions. This systematic review examines evidence of a relationship between childhood trauma/adverse life events and psychosis, especially in SCZ. A methodical search provided reproducible results using these five databases: PubMed, ScienceDirect, Semantic Scholar, JSTOR, and Cochrane Library. The systematic search focused on articles published between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Our exploratory analyses suggested that forms of neglect (emotional and physical) together with emotional abuse were the subtypes mostly contributing to cluster separation. This is consistent with evidence showing that the prevalence of child neglect is around 78% in the general population, while physical and sexual abuse are reported in around 18% and 9% [87].…”
Section: Antipsychotics Do Not Increase Netssupporting
confidence: 92%
“…Our exploratory analyses suggested that forms of neglect (emotional and physical) together with emotional abuse were the subtypes mostly contributing to cluster separation. This is consistent with evidence showing that the prevalence of child neglect is around 78% in the general population, while physical and sexual abuse are reported in around 18% and 9% [87].…”
Section: Antipsychotics Do Not Increase Netssupporting
confidence: 92%
“…Childhood trauma experiences are also associated with the degree of symptoms, with higher levels of trauma being associated with more positive symptoms, depressive symptoms, and lower levels of cognitive functioning. Childhood trauma experiences are associated more with positive symptoms, such as hallucinations and delusions, than with negative symptoms [5]. Childhood trauma induces dissociation, where stronger childhood trauma experiences are reflected by higher scores on the Dissociative Experiences Scale (DES), which measures dissociation.…”
Section: Clinical Overlap Between Scz and Tsrdmentioning
confidence: 99%
“…Positive symptoms have also been shown to correlate positively with DES scores in SCZ patients [28]. Indeed, some researchers have proposed the idea that symptoms such as hallucinations and delusions reflect a personal perception of intrusion that leads to a sense of hopelessness [5]. Furthermore, it is worth noting that the direction of Schneider's first-class symptoms, which were historically considered important symptoms of SCZ, are more common in patients with dissociative identity disorder than in those with SCZ [29].…”
Section: Clinical Overlap Between Scz and Tsrdmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that individuals engaged with mental health services report high levels of childhood and adulthood trauma (2, 810). There is a high prevalence of trauma among service users in acute services, including among women (2, 11), those with psychosis (12, 13), and “personality disorder” diagnoses (14) (which is a particularly controversial diagnosis (15) as a result of the stigma associated with this diagnostic label and disparities in quality of care experienced (1619)). Electronic health record evidence shows that service users with a history of abuse during childhood have more comorbidities and are more likely to have inpatient admissions versus service users without a similar history (20).…”
Section: Introductionmentioning
confidence: 99%